2006
DOI: 10.1158/0008-5472.can-06-2294
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Repair of the Oxidative 8-Oxoguanine DNA Damage and Risk of Head and Neck Cancer

Abstract: An increasing number of studies indicate that reduced DNArepair capacity is associated with increased cancer risk. Using a functional assay for the removal of the oxidative DNA lesion 8-oxoguanine by the DNA-repair enzyme 8-oxoguanine DNA glycosylase 1 (OGG1), we have previously shown that reduced OGG activity is a risk factor in lung cancer. Here, we report that OGG activity in peripheral blood mononuclear cells from 37 cases with squamous cell carcinoma of the head and neck (SCCHN) was significantly lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 32 publications
(36 reference statements)
5
70
0
Order By: Relevance
“…This approach assumes that (i) DNA repair activity in PBMC is a legitimate surrogate for DNA repair in other tissues, and (ii) each individual has a personal baseline capacity to repair DNA. These assumptions are supported by previous results showing that the activity of the DNA repair enzyme OGG1 in PBMC correlates to the activity in lung tissue (13), and that individuals exhibit a personal OGG1 activity that is stable over several years (13) and does not significantly change years after recovery from cancer (15). Using this approach we found that low OGG1 enzymatic activity is associated with the risk of lung cancer (13) and head and neck cancer (15).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…This approach assumes that (i) DNA repair activity in PBMC is a legitimate surrogate for DNA repair in other tissues, and (ii) each individual has a personal baseline capacity to repair DNA. These assumptions are supported by previous results showing that the activity of the DNA repair enzyme OGG1 in PBMC correlates to the activity in lung tissue (13), and that individuals exhibit a personal OGG1 activity that is stable over several years (13) and does not significantly change years after recovery from cancer (15). Using this approach we found that low OGG1 enzymatic activity is associated with the risk of lung cancer (13) and head and neck cancer (15).…”
Section: Introductionsupporting
confidence: 86%
“…These assumptions are supported by previous results showing that the activity of the DNA repair enzyme OGG1 in PBMC correlates to the activity in lung tissue (13), and that individuals exhibit a personal OGG1 activity that is stable over several years (13) and does not significantly change years after recovery from cancer (15). Using this approach we found that low OGG1 enzymatic activity is associated with the risk of lung cancer (13) and head and neck cancer (15). In addition, we found that increased enzymatic activity of MPG, a DNA repair enzyme of the DNA glycosylases family, which removes from DNA multiple alkylation and oxidative lesions, is associated with increased lung cancer risk (18).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, it was recently reported that in malignant tissues (in transitional meningioma and in glioblastoma multiforme) the degree of oxidative DNA damage (8OHdG) is increased whereas the total anti-oxidant capacity is decreased Tuzgen et al, 2007) Indeed, efficient DNA repair mechanisms comprise a critical component in the protection against cancer and among these the 8-oxoguanine DNA glycosylase (OGG1) enzyme is crucial for repairing the oxidative DNA lesion 8OHdG that is highly mutagenic and carcinogenic. Most importantly is that reduced activity of OGG1 is considered an established risk factor for various cancers such as lung and head and neck cancer (Paz-Elizur et al, 2006. Hence, the reduction observed in salivary OGG1 in the OSCC patients is expected.…”
Section: Discussionmentioning
confidence: 97%
“…8-Oxoguanine is a common mutagenic DNA lesion which is formed abundantly by intracellular oxidation and exogenous carcinogens like cigarette smoke (15,16). It has also been shown that cigarette smoke induces other forms of DNA damage, including single-strand breaks (SSBs) (17,18) and possibly double-strand breaks (DSBs) (19,20).…”
Section: Introductionmentioning
confidence: 99%